DAYA TARIK INVESTOR MEMODERASI HUBUNGAN GROWTH OPTION DAN STRATEGI BERSAING DENGAN KINERJA KEBERLANJUTAN (Studi Empiris Pada Perusahaan yang Terdaftar Index Kompas 100 Periode 2019 - 2023) - Rosana, Andri Murti; Holiawati; Ruhiyat, Endang (Jurnal Riset Terapan Akuntansi, 2025)
The purpose of this study is to test and analyze Investor Attractiveness Moderates the Relationship between Growth Option and Competitive Strategy with Sustainability Performance in companies listed on the Kompas 100 Index for the period 2019-2023. This study uses observational data from 100 companies and a sample of 35 companies from the Kompas 100 Index listed on the Indonesia Stock Exchange from 2019 to 2023. The data used are secondary data in the form of financial reports and sustainability reports of sample companies. Hypothesis testing is carried out using a panel data linear regression model and moderating regression analysis with Eviews 12 software. The results of this study indicate that Growth Option does not have a negative effect on Sustainability Performance, Competitive Strategy has an effect on Sustainability Performance, Investor Attractiveness does not moderate the relationship between Growth Option and Sustainability Performance. Investor Attractiveness does not moderate the relationship between Competitive Strategy and Sustainability Performance. This finding indicates that although investor attractiveness can reflect market perceptions of a company's potential, this factor has not been able to strengthen the influence of internal variables such as growth options and competitive strategies on sustainability performance. This is due to the dominance of short-term profit motives among Indonesian capital market investors, who have not fully integrated sustainability aspects into the investment decision-making process. Therefore, companies need to show investors the importance of developing adaptive and sustainable strategies, which not only provide short-term but also long-term financial benefits for investors, and not only prioritize financial benefits, but are more complete by integrating social and environmental aspects. This study provides an important contribution to the development of sustainability management literature and corporate strategy, especially in the context of the Indonesian capital market. Keywords: Investor Attraction, Growth Options, Competitive Strategy, Sustainability Performance